Global assessment report on disaster risk reduction - Costs and benefits of early warning systems - Rogers, David; Tsirkunov, Vladimir (United Nations International Strategy for Disaster Reduction (UNISDR), 2011)
Keywords: Ouvrage_Collectif_Numéro1

La méthode hydrogéomorphologique de détermination des zones inondables - Ballais, Jean-Louis; Chave, Sylvain; Dupont, Nadia; Masson, Éric; Penven, Marie-Josée (Physio-Géo. Géographie physique et environnement, 2011)
L'ouvrage fait le point sur les développements de la méthode mise au point dans les années 1980 et présentée en détail pour la première fois en 1996. Il s'organise en deux grandes parties : la présentation de la méthode hydrogéomorphologique de détermination des zones inondables et les applications de cette méthode. La première partie justifie d'abord la nécessité de mettre au point et d'utiliser une nouvelle méthode face aux insuffisances des méthodes hydrologiques-hydrauliques utilisées en France (et très généralement dans le monde) pour la prévision et la prévention des risques d'inondation.Elle présente ensuite les principes de la méthode (chapitre II). C'est ainsi qu'elle consacre un long développement au rôle fondamental de la géomorphologie, tout particulièrement aux quatre lits qu'un cours d'eau peut occuper en fonction de son débit, lits déterminés par l'analyse de la microtopographie de la plaine alluviale fonctionnelle complétée par leur caractérisation sédimentologique. L'influence de la lithologie et de la tectonique est ensuite évoquée. Un deuxième sous-chapitre présente les critères complémentaires : la couverture végétale naturelle et l'occupation humaine au travers de la localisation des constructions, des vestiges historiques et archéologiques, de l'adaptation de l'activité agricole aux caractéristiques de la plaine alluviale et de la structure du parcellaire. Un troisième sous-chapitre regroupe les facteurs de variation : les grandes zones climatiques et les facteurs anthropiques (travaux et ouvrages hydrauliques, pratiques agricoles, imperméabilisation des sols due à l'urbanisation). Enfin, l'évolution au cours de la période historique des unités hydrogéomorphologiques principales, lit mineur et lit majeur, est présentée.Le court chapitre III met en relation l'hydrogéomorphologie et le fonctionnement hydraulique à l'échelle des unités hydrogéomorphologiques puis au niveau de la modélisation. La deuxième partie présente les trois principales applications de la méthode : la cartographie des zones inondables, la méthode intégrée et l'aménagement. La cartographie des zones inondables est actuellement la principale application, grâce à son intégration dans la politique de prévision et de prévention des risques d'inondation en France depuis 1995. Le chapitre qui lui est consacré s'articule en trois ensembles. Le premier est un rappel critique des moyens techniques d'acquisition des données : cartes, photographies aériennes, imagerie satellite en plein développement, données relatives aux crues historiques, observations de terrain. Le deuxième sous-chapitre détaille la cartographie des données sous la forme de la carte hydrogéomorphologique ou carte d'inondabilité hydrogéomorphologique en faisant l'historique et la critique de la légende proposée par le Ministère de l'Écologie français, puis en traitant plusieurs problèmes de cartographie : l'exhaussement du lit majeur, l'adoucissement du talus externe de la plaine alluviale fonctionnelle par le ruissellement diffus, le recouvrement du talus de la terrasse alluviale par le colluvionnement, la représentation du lit majeur exceptionnel et de la terrasse alluviale holocène, le cas spécifique des vallons secs. Enfin, les premières cartographies réalisées à l'étranger sont présentées. Un court dernier sous-chapitre traite de l'interprétation, qualitative et semi-quantitative, de la carte hydrogéomorphologique.La méthode intégrée, qui reste pour l'essentiel au stade expérimental, est présentée dans le chapitre II : d'abord ses origines, puis ses principes, puis ses premières applications prometteuses en France.Le chapitre III regroupe les potentialités, importantes mais peu exploitées, de la méthode hydrogéomorphologique pour l'aménagement des plaines alluviales, en insistant sur deux points : les conséquences de l'exhaussement des lits majeurs et le fonctionnement des cours d'eau pendant les crues exceptionnelles. La conclusion générale insiste sur l'efficacité de cette méthode, née de la problématique des risques naturels et hors du champ académique, ainsi que sur sa fécondité, en particulier la découverte de nouveaux objets géomorphologiques comme le lit majeur exceptionnel et de nouveaux concepts comme celui de débit hydrogéomorphologique.
Number: Volume 5 Publisher: Martin, Claude
Keywords: Ouvrage_Collectif_Numéro1

Emotions, Trust, and Perceived Risk: Affective and Cognitive Routes to Flood Preparedness Behavior - Terpstra, Teun (Risk Analysis, 2011)
Despite the prognoses of the effects of global warming (e.g., rising sea levels, increasing river discharges), few international studies have addressed how flood preparedness should be stimulated among private citizens. This article aims to predict Dutch citizens’ flood preparedness intentions by testing a path model, including previous flood hazard experiences, trust in public flood protection, and flood risk perceptions (both affective and cognitive components). Data were collected through questionnaire surveys in two coastal communities ( n = 169, n = 244) and in one river area community ( n = 658). Causal relations were tested by means of structural equation modeling (SEM). Overall, the results indicate that both cognitive and affective mechanisms influence citizens’ preparedness intentions. First, a higher level of trust reduces citizens’ perceptions of flood likelihood, which in turn hampers their flood preparedness intentions (cognitive route). Second, trust also lessens the amount of dread evoked by flood risk, which in turn impedes flood preparedness intentions (affective route). Moreover, the affective route showed that levels of dread were especially influenced by citizens’ negative and positive emotions related to their previous flood hazard experiences. Negative emotions most often reflected fear and powerlessness, while positive emotions most frequently reflected feelings of solidarity. The results are consistent with the affect heuristic and the historical context of Dutch flood risk management. The great challenge for flood risk management is the accommodation of both cognitive and affective mechanisms in risk communications, especially when most people lack an emotional basis stemming from previous flood hazard events.
Keywords: Ouvrage_Collectif_Numéro1

Economic development and losses due to natural disasters: The role of hazard exposure - Schumacher, Ingmar; Strobl, Eric (Ecological Economics, 2011)
MAG ID: 1995943259

Normalizing Economic Loss from Natural Disasters: A Global Analysis - Neumayer, Eric; Barthel, Fabian (Global Environmental Change-human and Policy Dimensions, 2011)
Abstract Climate change is likely to lead to an increase in the frequency and/or intensity of certain types of natural hazards, if not globally, then at least in certain regions. All other things equal, this should lead to an increase in the economic toll from natural disasters over time. Yet, all other things are not equal since affected areas become wealthier over time and rational individuals and governments undertake defensive mitigation measures, which requires normalizing economic losses if one wishes to analyze trends in economic loss from natural disasters for detecting a potential climate change signal. In this article, we argue that the conventional methodology for normalizing economic loss is problematic since it normalizes for changes in wealth over time, but fails to normalize for differences in wealth across space at any given point of time. We introduce an alternative methodology that overcomes this problem in theory, but faces many more problems in its empirical application. Applying, therefore, both methods to the most comprehensive existing global dataset of natural disaster loss, in general we find no significant upward trends in normalized disaster damage over the period 1980–2009 globally, regionally, for specific disasters or for specific disasters in specific regions. Due to our inability to control for defensive mitigation measures, one cannot infer from our analysis that there have definitely not been more frequent and/or more intensive weather-related natural hazards over the study period already. Moreover, it may still be far too early to detect a trend if human-induced climate change has only just started and will gain momentum over time.
MAG ID: 3022174945

The Economics of Natural Disasters - Kellenberg, Derek; Mobarak, A. Mushfiq (Annual Review of Resource Economics, 2011)
This review discusses the ways in which countries are affected by natural disasters, depending on their socioeconomic characteristics, their level of development, and their inherent levels of natural disaster risk. We also explore various aspects of ex ante disaster mitigation such as improvements in natural disaster risk information and natural disaster insurance markets, as well as ex post responses to natural disaster in the form of postdisaster aid and long-run growth prospects. By highlighting some of the recent findings in this literature, we synthesize what we know about the economics of natural disasters and identify research areas of interest for future work.
MAG ID: 1976407278

Flood risk, vulnerability and environmental justice: Evidence and evaluation of inequality in a UK context - Walker, Gordon; Burningham, Kate (Critical Social Policy, 2011)
Flooding has only relatively recently been considered as an environmental justice issue. In this paper we focus on flooding as a distinct form of environmental risk and examine some of the key evidence and analysis that is needed to underpin an environmental justice framing of flood risk and flood impacts. We review and examine the UK situation and the body of existing research literature on flooding to fill out our understanding of the patterns of social inequality that exist in relation to both flood risk exposure and vulnerability to the diverse impacts of flooding. We then consider the various ways in which judgements might be made about the injustice or justice of these inequalities and the ways in which they are being sustained or responded to by current flood policy and practice. We conclude that there is both evidence of significant inequalities and grounds on which claims of injustice might be made, but that further work is needed to investigate each of these. The case for pursuing the framing of flooding as an environmental justice issue is also made.
MAG ID: 2099524802